Move: Durational Dance-Making as We Age - Nikolai, Jennifer (Frontiers in Sports and Active Living, 2022)
Dance making and moving support a positive aging approach to aesthetic, cultural, and social meanings, thus, shaping dancers' lives. My perspective is informed by making dance a durational and sustained practice in the life of a long-life mover. Positioned as a practice-oriented researcher, I am surrounded by inspiring authors and artists who embrace maturity with improvisational making. This perspective piece reflects on making Move, a durational practice-oriented research process. Move contextualizes durational elements that I associates with the life of a mover; my writing and my companions improvising with my hand-held camera in isolation, in my neighborhood on Tāmaki Makaurau/Auckland's North Shore.This perspective piece opens a process I refer to as a camera-dancer dyad, a duet between a dancer and a camera, making in isolation as we age. Furthermore, by embracing the accessibility of everyday recording devices as dancing partners, dance making with mobile cameras becomes a playful partnership with a long life.